Gabonese parliamentarians in the Grand Council of French Equatorial Africa and the expression of Gabonese protonationalism (1946-1959) - (:unkn) unknown (My University, 2023)
The Grand Council of French Equatorial Africa (1946-1959), bringing together the parliamentarians of this colonial entity, was a space of ideological confrontation. Despite the communitarization of local political life, this federal assembly ultimately a place of expression of Gabonese protonationalism, based on a feeling of injustice.
Keywords: African Research